Critical functions for STAT5 tetramers in the maturation and survival of natural killer cells - Jian-Xin Lin; Ning Du; Peng Li; Majid Kazemian; Tesfay Gebregiorgis; Rosanne Spolski; Warren J. Leonard (Nature Communications)
Abstract Interleukin-15 (IL-15) is essential for the development and maintenance of natural killer (NK) cells. IL-15 activates STAT5 proteins, which can form dimers or tetramers. We previously found that NK cell numbers are decreased in Stat5a−Stat5b tetramer-deficient double knockin (DKI) mice, but the mechanism was not investigated. Here we show that STAT5 dimers are sufficient for NK cell development, whereas STAT5 tetramers mediate NK cell maturation and the expression of maturation-associated genes. Unlike the defective proliferation of Stat5 DKI CD8+ T cells, Stat5 DKI NK cells have normal proliferation to IL-15 but are susceptible to death upon cytokine withdrawal, with lower Bcl2 and increased active caspases. These findings underscore the importance of STAT5 tetramers in maintaining NK cell homoeostasis. Moreover, defective STAT5 tetramer formation could represent a cause of NK cell immunodeficiency, and interrupting STAT5 tetramer formation might serve to control NK leukaemia.